(untitled) (Visnyk NTUU KPI Seriia - Radiotekhnika Radioaparatobuduvannia, 2014)
Introduction. In this paper is presented a theoretical basis of chaotic Rossler system. Modelling of Chaotic Rossler System in LabView. Submitted programming interface that has been developed in LabView software environment. It allows generating and researching chaotic Rossler system. Submitted by time distribution of three chaotic coordinates and spectral analysis. Also submitted values of variables in which generated different period (controlled) attractors of the chaotic Rossler system. The software interface demonstrates masking and decrypt information carrier of the chaotic Rossler system. Modelling of Chaotic Rossler System in MultiSim. Using MultiSim software environment conducted scheme technical analysis circuit of a generator that implements a chaotic Rossler system. Conclusions. Modelled circuit of generator confirming correspondence scheme-technical solution to mathematical apparatus that describing chaotic Rossler system. Keywords: chaos; control; system; Rossler; LabView; MultiSim